Creativity Assessment in English Writings of University Students: An Application of Four-C Model of Creativity” (mini-c, little-c, Pro-c, and Big-C) - Muhammad Kashif; Dr. Jabir Hussain; Madeeha Dustgir, (Dialogue Social Science Review (DSSR), 2025)
The concept of creativity is as old as the history of the world. Creativity is directly related to mental health and growth so creativity is born with living organisms having a brain like human beings or other animals. Assessment of any idea was generated with the emergence of that specific field or ideology so the synthesis can be made that creativity assessment is as prior as the history of the world. In this paper, the researcher tried to find out the solutions and different ways of language competency improvement tools and categorize the creativity level of the university students according to the Four-C Model of Creativity” (mini-c, little-c, Pro-c, and Big-C) proposed by Kaufman and Beghetto. Creativity is defined as the ability to find out the problem solutions differently from the others. Creativity is defined as moving from familiar to unfamiliar. Creativity is how any layman can prove him superior by realizing his works are done differently, accurately, and perfectly in comparison with all others. Researchers in this field attempted to measure and define creativity by answering two major questions what are the types of assessment of creativity in English writings of university students? And what are the creative activities to evaluate the second language competence of university students? This chapter gives a brief overview of creativity and creativity assessment tools and categorization.